Amino Acids, Peptides and Proteins. - Barrett, G. C. (Specialist periodical report., 2002)
In an ever-increasing domain of activity Amino Acids Peptides and Proteins provides an annual compilation of the world's research effort into this important area of biological chemistry. Volume 33 provides a review of literature published during 2000. Comprising a comprehensive review of significant developments at this biology/chemistry interface each volume opens with an overview of amino acids and their applications. Work on peptides is reviewed over several chapters ranging from current trends in their synthesis and conformational and structural analysis to peptidomimetics and the discover.